Oxidation of Some Ortho-substituted Phenyl Methyl Sulphides with Quinolinium Fluorochromate in Acetonitrile Medium - Meenakshisundaram, Subbiah (Asian Journal of Chemistry, 2012)
The kinetics of oxidation of some ortho-substituted phenyl methyl sulphides with quinolinium fluorochromate (QFC) has been investigated in acetonitrile medium. Regression analysis was done with Taft’s linear free-energy polar-energy relationship and linear free-energy steric-energy relationship. Steric contribution to this reaction seems to be much less than the polar effect. Analysis of rate data with LD and LDS equations emphasizes that localized effect plays a predominate role in this oxidation.